Sistem Rekomendasi Destinasi Pariwisata Menggunakan Metode Hibrid Case Based Reasoning dan Location Based Service Sebagai Pemandu Wisatawan di Banyuwangi - Kusuma, Dedy Hidaya; Shodiq, Moh. Nur (Universitas Nusantara PGRI Kediri, 2017)
As one of the fastest growing tourist destinations, the number of tourist arrivals in Banyuwangi Regency shows a significant growth where in the range of 2010 - 2015 there is an increase of domestic tourists by 161% and abroad by 210%. The increase in tourist numbers is not a trouble-free process, especially with regard to visitor preferences that change over time. Tourist information and a variety of tourist interests often make tourists confused in determining the choice of any destination to visit. While Banyuwangi tourism information that is available in printed form or that can be accessed online still requires tourists to sort and choose their own in accordance with the interests and preferences so that tourists need any suggestions or recommendations. In the field of tourism, this recommendation may include objects to be visited, existing tourist events, travel schedules, travel routes, availability of infrastructure and so forth. The recommendation system proposed in this research uses a combination of (hybrid) case-based reasoning and location-based methods. The system is built in the form of android based mobile applications. Input from users to the system of travelers preferences include tourist types, tariff categories, modes of transportation, and tourism activities. These preferences together with user location based on GPS coordinates are further compared to the tourist object attributes stored on the system using the nearest neighbor similarity method. The output of the system in the form of recommendation of tourism object that has the highest similarity to the user preference. The results of this study are expected to assist tourists in choosing tourism objects in Banyuwangi according to their preferences or demand criteria.